2013
DOI: 10.1242/dev.090860
|View full text |Cite
|
Sign up to set email alerts
|

The transcription factor Otx2 regulates choroid plexus development and function

Abstract: SUMMARYThe choroid plexuses (ChPs) are the main regulators of cerebrospinal fluid (CSF) composition and thereby also control the composition of a principal source of signaling molecules that is in direct contact with neural stem cells in the developing brain. The regulators of ChP development mediating the acquisition of a fate that differs from the neighboring neuroepithelial cells are poorly understood. Here, we demonstrate in mice a crucial role for the transcription factor Otx2 in the development and maint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
109
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(112 citation statements)
references
References 47 publications
(53 reference statements)
3
109
0
Order By: Relevance
“…Consistent with previous microarray analyses (Beckervordersandforth et al, 2010; Johansson et al, 2013; Ninkovic et al, 2013; Pinto et al, 2009, 2008; Stahl et al, 2013; Walcher et al, 2013), quantitative reverse transcription polymerase chain reaction (qRT‐PCR) confirmed the changes observed in the microarray (Fig. 3D), including the strongly upregulated genes Lgals1 (lectin, galactoside‐binding, soluble, 1) and Lgals3 (lectin, galactoside‐binding, soluble, 3) (40× and 10×, respectively).…”
Section: Resultssupporting
confidence: 90%
“…Consistent with previous microarray analyses (Beckervordersandforth et al, 2010; Johansson et al, 2013; Ninkovic et al, 2013; Pinto et al, 2009, 2008; Stahl et al, 2013; Walcher et al, 2013), quantitative reverse transcription polymerase chain reaction (qRT‐PCR) confirmed the changes observed in the microarray (Fig. 3D), including the strongly upregulated genes Lgals1 (lectin, galactoside‐binding, soluble, 1) and Lgals3 (lectin, galactoside‐binding, soluble, 3) (40× and 10×, respectively).…”
Section: Resultssupporting
confidence: 90%
“…The Otx2 gene, which encodes a transcription factor containing a homeodomain important for the development of the CNS, plays a major role in the formation of the plexuses. Indeed, the four plexuses are absent after conditional deletion of this gene at E9 in mice [64]. Both proliferation and differentiation of choroidal epithelial cells are dependent on Notch signalling and neurogenin2 [60].…”
Section: Understanding Choroid Plexus Developmentmentioning
confidence: 99%
“…By dynamically altering its secretome in response to input signals, the choroid plexus modulates stem cell behaviour in adult neural stem cell niches, can affect physiology and contribute to pathology function is key to normal brain development, as inherited or acquired choroidal folate transport defects induce cerebral folate deficiency that translate into severe childhood neurodegenerative diseases [54,142], and may be a main contributor to the encephalopathy associated with the Kearns Sayre syndrome [141]. Due to the flow of the CSF through the ventricular system, factors can exert long-range, as well as regionally distinct effects, depending on local concentration gradients of individual factors and the repertoire of receptors and modulators expressed by the responding cells [64].…”
Section: Embryonic and Postnatal Developmentmentioning
confidence: 99%
“…23 Normal production and circulation of the CSF are known to be crucial for proper brain development. 24,25 For example, Wnt4 and Wnt modulator Tgm2 are regulated by Otx2, a master regulator of choroid plexus development which produces CSF. 24 We showed recently that Ulk4 is essential for ciliogenesis and CSF flow.…”
mentioning
confidence: 99%
“…24,25 For example, Wnt4 and Wnt modulator Tgm2 are regulated by Otx2, a master regulator of choroid plexus development which produces CSF. 24 We showed recently that Ulk4 is essential for ciliogenesis and CSF flow. 26 Ependymal layer constitutes polarized cells with motile cilia projecting to ventricles, and the planar cell polarity cadherins Celsr2 and Celsr3 are shown to regulate basal body orientation at the foot of cilia.…”
mentioning
confidence: 99%